Prevalence of oral habits in a child population in Trinidad, West Indies. Issue 3 (December 2017) - Percival, Tricia M.; Smith, William A.J.; Smith, Keisha F.
Abstract: Objectives: The purpose of this study was to determine the prevalence of oral habits (both nutritive and non-nutritive) in children in Trinidad, West Indies and to determine if there are any associated factors such as age, gender, ethnicity, social/familial factors, dietary practices and parental perception. Methods: 155 children aged 4–16 years and their parents were questioned using a structured interview about breast and bottle feeding history, history of oral habits, sibling habit history, parental education level and habit history and parental belief and perception. Oral habits such as pacifier use, digit sucking, tongue sucking, lip biting and sucking, nail biting, and object chewing were recorded. Results: There was a very high prevalence of oral habits (91.6%) with 63.9% of children having two or more habits. The most common oral habit was nail biting (52.9%) and ice crunching was most commonly found in females. Tongue sucking was predominant in children of African ethnicity. Oral habits were more common in children whose parents had a post primary education. 51% of parents were not concerned about oral habits and 64.5% believed that the child would stop the habit without any intervention. Conclusion: The prevalence of both nutritive and non-nutritive oral habits in Trinidad are high and some associations were found with gender, ethnicity, social, dietary and familial factors.